Problem solving and data analysis using Minitab : a clear and easy guide to six sigma methodology - Khan, Rehman M. (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
"Problem Solving and Data Analysis using Minitab presents example based learning to aid readers in understanding how to use MINITAB 16 for statistical analysis and problem solving"--
9.1 What are Correlation and Regression?9.2 Correlation; 9.3 Multiple Correlations; 9.4 Introduction to Regression; 9.5 Single Predictor Regression; 9.6 Introduction to Multiple Predictor Regression; 9.7 Multiple Predictor Regression; 9.8 Predictor Selection Procedure; 9.9 Nonlinear Regression; Chapter 10 Design of Experiment; 10.1 Why Use Design of Experiment?; 10.2 Types of DOE; 10.3 DOE Terminology; 10.4 Two Level Factorial Designs; 10.5 Fractional Factorial Designs; Chapter 11 Help; 11.1 Help Overview; 11.2 Help! Help!; 11.3 Tutorials; 11.4 StatGuide; 11.5 Methods and Formulas.
Includes index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Minitab; Minitab; Minitab; Mathematical statistics -- Data processing; Problem solving -- Statistical methods; Six sigma (Quality control standard); MATHEMATICS -- Probability & Statistics -- General; Mathematical statistics -- Data processing; Problem solving -- Statistical methods; Six sigma (Quality control standard); Electronic books; Electronic books; Electronic books